Exploring women’s retirement literature through bibliometric analysis using vosviewer - Noredi E.A., Mohamad; Halimatul Nadia, Zainuddin; Rajadurai, Jegatheesan; Noraina Mazuin, Sapuan (Faculty of Economics and Administration, 2023)
This paper aims to analyse the issue of women’s retirement (WR) literature through bibliometric analysis using VOSviewer, a programme for the visualisation of similarities (VOS). Publications focusing on women’s retirement were compiled from the Scopus database, with a total of 393 items spanning the years 1965 to 2021. The most prolific nations for retirement literature are the United States, United Kingdom, and Sweden, which reflects the affiliation analysis that correlates highly with published papers within specific institutions in those three countries. The issues were discussed within the context of social sciences, economics, econometrics, and finance, as well as psychology. This suggests an interlinking of women’s retirement with social and financial issues that might contribute towards psychological challenges for women. The most cited keywords, among others, are ‘retirement’, ‘women’ and ‘pension’, with thematic clusters being linked to ‘ageing’ and ‘health’. These could be linked to health problems that emerge because of ageing, and thus might be linked to the retirement wellbeing of women. The findings of this paper shed light on several implications that can be used as a guideline for researchers and act as a foundation before embarking on the emerging knowledge areas of women’s retirement.